Tecnologias, educação e recursos audiovisuais: proposta de produto para curadoria de conteúdos - Oliveira, Lucas Augusto Ferreira (2020)
Thanks to the development of new tools and methods that have made geographical distances less relevant, education has been increasingly transformed. However, as the years progress, teaching and fostering student interest has become an increasingly complex and challenging activity, as the amount of disorganized and fragmented information that reaches young people rivals in the dispute with other everyday activities. In addition, media consumption, whether through streaming platforms, TV or the Internet, has increased day by day. Therefore, it is important to understand how the school should reinvent itself and how media content needs to be seen by educators as valid ways of building knowledge. This work, in addition to reviewing the literature on the use of audiovisual in education and on content curation, brings a product application plan for a digital tool that mixes media and didactic content for use by teachers, initially Brazilian, public and private basic education networks.